Antibacterial Activity of Bidara Leaf Extract (Ziziphus mauritiana) Against Staphylococcus aureus Isolated from Mastitis Case In Vitro - Saraswati, Afif Tasya; Sugihartuti, Rahmi; Puspitasari, Yulianna; Witaningrum, Adiana Mutamsari; Rachmawati, Kadek; Maslachah, Lilik; Raharjo, Hartanto Mulyo; Hisyam, Mirza Atikah Madarina; Tacharina, Martia Rani (Universitas Airlangga, 2023)
This research aimed to know the antibacterial activities of bidara leaf extract against Staphylococcus aureus isolated from mastitis cases. The isolate was identified before the antibacterial test. This study was done by five times repetitions on Mueller Hinton Agar. The concentrations used in this study were 30%, 40%, and 50% of bidara leaf extract then a blank disc was dipped into each concentration. Tetracycline disc was used as a positive control and aquadest was used as a negative control. The diameter of the clear zone was measured using calipers after incubation for 24 hours at 37â„ƒ. The results showed significant differences (p<0.05) between the positive control (K+), negative control K (-), and the concentration group. However, each concentration of bidara leaf extract showed insignificant differences in the diameter of the clear zone. It could be concluded that bidara leaf extract has antibacterial activities against Staphylococcus aureus isolated from mastitis cases.